Human undulatory swimming: kinematics, flow and mechanical model - Hochstein, S.; Blickhan, R. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: We have learned that athletes in high level swimming try to copy successful strategies from fish locomotion. They use underwater undulatory motion, also called dolphin kicks, to reach an optimum motion by filed kinematics. Due to the absence of systematic studies intensive training phases are necessary to check in the trialerror- principle the advantages and disadvantages of different variations of the motion. The aim of this study is to understand the motion in its fluid mechanical impact and to develop a motion pattern for optimum and efficient propulsion with the help of modern experimental and numerical flow analysis. METHODS: Time resolved particle image velocimetry (PIV) was used to visualize the flow around a swimmer during underwater undulatory swimming in still water in an indoor pool. The principle of PIV is to calculate the displacement of a large number of small levitating particles (diameter: 100 ìm, typically illuminated using green laser light) of two consecutive pictures. The path of the particles was monitored at 250 fps with a high speed video camera (PHOTRON Ultima APX). Local flow velocities and the velocity field were calculated by a cross-correlation algorithm. Swimmers kinematics were recorded using active LED marker at the joints and a video camera system (BASLER A602fc, 30 fps). RESULTS: Vortex generation is monitored in the head region and mainly in the region of the legs. The human